Case Report on Long COVID-19 - Kamath, Ganesh; Mani, Muthukumar; Poojary, Nagarathna (Journal of Pharmacy Practice and Community Medicine)
COVID-19 has dominated the whole world and resulted in increased morbidity and mortality. Here we present a case report of 54-years-old man with repeated admissions to the hospital after severe COVID-19 pneumonia which on progression lead to sepsis with bronchitis. There was Dexamethasone induced hyperglycaemia and was administered with antibiotics, corticosteroids, anti-asthmatics and COPD preparations. He was recurrently admitted to hospital for 4 times and was on oxygen support. These recurrent admissions lead to decreased quality of life and increased healthcare cost. Polypharmacy was on peak and underlying condition was not subsided. Prompt diagnosis and early interventions regarding COVID-19 complications must include a good scientific approach.
Keywords: Pneumonia; Bronchitis; COVID-19; Sepsis; Hyperglycemia; Polypharmacy.